Geography and correlates of attitude toward Female Genital Mutilation (FGM) in Sudan: What can we learn from successive Sudan opinion poll data?. (February 2016) - Hamilton, Alexander; Kandala, Ngianga-Bakwin
Highlights: Sudan is among Sub-Saharan Africa countries with high prevalence of FGM. However, comparison of recent surveys shows a decrease in the practice. Pro-anti FGM rates vary between different states of the country. We observed a decrease of pro-FGM with striking variation between states. Local pro-FGM monitoring leads to design of interventions with local impact. Abstract: In Sudan, prevalence of FGM is declining; likely as a result of changing attitude surrounding FGM, as more women believe the practice should be discontinued amid growing awareness about its health dangers. DFID Sudan opinion poll data collected from 2012 to 2014 was used. Bayesian geo-additive mixed models were used to map the spatial distribution of the likelihood of pro-FGM attitude at the state-level accounting for associated risk factors. During 2012 to 2014, the overall proportion of pro-FGM was 27.5% and 18.3% respectively with striking variations within states. People with pro-FGM attitude were more likely to be un-educated, living in rural settings with strong tribal identity. Individuals from Darfur were more likely to be pro-FGM when compared to the North state. The decrease in the practice of cutting observed between the 2006 and 2010 Sudanese Household Surveys and the resulting shift in attitude make a compelling case for public health policy to eradicate the FGM practice.